(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
In this work, silica aerogels were incorporated with high-performance Kevlar fabrics by coating to deal with heat transfer problems under a severe environment. Thermal protective properties of the prepared fabrics were evaluated by using a laser system coupled with a thermometer which records the back-surface temperature of the fabric under laser radiation. The effect of aerogel content as well as pixel time used for laser radiation on thermal protection was investigated and discussed. Meanwhile, thermal properties of the fabrics under ambient temperature were tested with a thermal camera, thermal insulation values of the fabrics with different coatings were compared and analyzed. Moreover, fly ash nanoparticles were used for coating as well to investigate their effect on thermal performance. The findings in this study can be used for further research in aerogel-based high-performance materials for thermal protection.